Pengaruh Sales Growth, Financial Distress, dan Transfer Pricing terhadap Tax Avoidance: Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Sektor Pertambangan tahun 2019-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
Tax constitutes the main source of revenue for the Indonesian government. The government continuously strives to improve tax compliance and system efficiency each year. Indonesia’s tax ratio in 2023, which stood at 10.31%, indicates a significant potential for tax avoidance. This study aims to empirically examine the effect of sales growth, financial distress, and transfer pricing on tax avoidance in mining sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The data used in this study are secondary data obtained from financial statements published on the official IDX website. The research population consists of 90 companies, with 280 observations selected using purposive sampling. Data analysis was performed using EVIEWS software. The results show that sales growth has no effect on tax avoidance, financial distress has a positive effect on tax avoidance, and transfer pricing has a negative effect on tax avoidance.